2007
DOI: 10.1177/0969733007073700
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Perceptions of Conscience Questionnaire

Abstract: Health care often involves ethically difficult situations that may disquiet the conscience. The purpose of this study was to develop a questionnaire for identifying various perceptions of conscience within a framework based on the literature and on explorative interviews about perceptions of conscience (Perceptions of Conscience Questionnaire). The questionnaire was tested on a sample of 444 registered nurses, enrolled nurses, nurses' assistants and physicians. The data were analysed using principal component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
130
2
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(159 citation statements)
references
References 40 publications
4
130
2
11
Order By: Relevance
“…From a theological perspective, a bad or troubled conscience can be absolved by forgiveness (Saarisalo and Koilo 1973, p. 3964). Recently, the investigation of health care personnel's perceptions of conscience in caring (in for example, Sweden), began with an extensive literature review by Dahlqvist et al (2007). The review revealed that the main theories on conscience were picked up from the work of known philosophers and psychoanalysts.…”
Section: Stress Of Conscience: a Theological Perspective On Moral Dismentioning
confidence: 98%
See 3 more Smart Citations
“…From a theological perspective, a bad or troubled conscience can be absolved by forgiveness (Saarisalo and Koilo 1973, p. 3964). Recently, the investigation of health care personnel's perceptions of conscience in caring (in for example, Sweden), began with an extensive literature review by Dahlqvist et al (2007). The review revealed that the main theories on conscience were picked up from the work of known philosophers and psychoanalysts.…”
Section: Stress Of Conscience: a Theological Perspective On Moral Dismentioning
confidence: 98%
“…In the empirical research regarding stress of conscience, Dahlqvist et al (2007) suggested that the conscience is the ''cornerstone of ethics''. Glasberg's et al (2006) explanation of stress of conscience is similar to that of moral distress and moral stress-for example, they note that ''stress in health care is affected by moral factors.…”
Section: Stress Of Conscience: a Theological Perspective On Moral Dismentioning
confidence: 99%
See 2 more Smart Citations
“…Il en ressort que, lorsque ces professionnelles sont sommées d'agir en fonction de directives administratives sans lien avec des normes morales jugées respectables, elles peuvent souffrir moralement. En effet, juger qu'en fonction de commandes prescriptives de l'organisationemployeur on peut se conduire de mauvaise manière, de façon a-déontologique envers la clientèle, est susceptible d'engendrer une souffrance et d'avoir de graves répercussions sur le bien-être des professionnelles (Curchod, 2009;Vézina, 2008;Béland, 2009;Lützén, et collab., 2003;Dahlqvist, et collab., 2007;Gustafsson, Norberg et Strandberg, 2008;Meylan, Boillat et Morel, 2009;Nathaniel, 2006;Dahlqvist, Söderberg et Norberg, 2009;Kopala et Burkhart, 20058;Pendry, 2007).…”
Section: Les Modèles Causalistesunclassified